Efeitos do exercício físico sobre a atividade de enzimas dos sistemas purinérgico e colinérgico em sangue de ratos hipertensos - Cardoso, Andréia Machado (2014)
Hypertension is a multifactor clinical condition, which is accompanied by a low-grade inflammation and alterations in platelet function. These modifications may be related to an imbalance in the regulation of adenine nucleotides (ATP, ADP and AMP), adenosine and acetylcholine (ACh) levels. This regulation is performed by purinergic [NTPDases, ecto-5 - nucleotidase and adenosine deaminase (ADA)] and cholinergic [Acetylcholinesterase (AChE) and Butyrylcholinesterase (BuChE)] system enzymes, present in blood, respectively. These enzymes can be modulated by regular practice of physical exercise, which has been recommended for the treatment of hypertension. Thus, the aim of this study was to investigate the effect of six swimming training weeks on blood pressure, on purinergic and cholinergic systems enzymes activities in blood as well as on platelet aggregation and classic inflammatory markers in rats with hypertension induced by methyl Nω-nitro-L-arginine ester hydrochloride (L-NAME) administration. In order to better understand chronic changes, we also evaluated the effect of a single acute bout of exercise on the activity of the enzymes already mentioned. The animals were divided into four groups (n = 10): control, exercise, LNAME and exercise L-NAME. After 60 days of treatment, animals were euthanized and platelets, lymphocytes, whole blood and serum were used for experimental determinations. The results showed that swimming training was able to reduce blood pressure in hypertensive rats, and to prevent the increase in NTPDase, ecto-5'-nucleotidase and ADA activities in lymphocytes and platelets. This probably contributed in preventing platelet aggregation. Chronically, swimming was also effective in preventing the increase in AChE (in lymphocytes and whole blood) and BuChE (in serum) activities. Regarding to the expression of NPTDase1, exercise per se triggered a reduction in the expression of this enzyme, but had no significant effects in hypertensive rats. The prevention of the increase in cholesterol, triglycerides, C-reactive protein levels and myeloperoxidase activity generated by swimming practice reinforces the fact that exercise reduced inflammation in hypertensive rats. In response to a single acute bout of exercise, was observed an increase in the activity of cholinergic system enzymes in whole blood, lymphocytes and serum, and purinergic system enzymes in platelets. However, there was a decrease in the activity of NTPDase and ADA in lymphocytes. It can be concluded that this study allowed us to unveil, in part, the mechanisms related to the protective processes arising from regular physical exercise on hypertension related to inflammation and platelet aggregation. The results also reinforce the importance of measuring the purinergic and cholinergic systems enzymes as parameters of inflammatory response. Also, it is concluded that regular physical exercise has antithrombotic and anti-inflammatory effects by modulating the activity purinergic and cholinergic systems enzymes in hypertension. It is suggested that these responses have been derived from the adaptations that occur in the body due to each acute stimulus that promotes enough impact to break homeostasis and promote beneficial adaptations. Thus, moderate aerobic exercise has a key role in acting as an adjuvant in the treatment of hypertension.